2014
DOI: 10.1007/s00268-014-2698-5
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Complications After Pancreaticoduodenectomy: Skinny Bile Ducts Are Surgeons’ Enemies

Abstract: The only identified predictive factor of BC, either a BS or a BL, was a thin bile duct. Although the noninvasive technique was the treatment of choice initially, reintervention was required in almost 25 % of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 27 publications
4
53
2
1
Order By: Relevance
“…First, the common hepatic duct (CHD) size of patients with a stent must be larger than that of those without one, even after biliary decompression. Duconseil et al demonstrated that bile duct size <5 mm was significantly associated with the occurrence of biliary stricture, and the only identified risk factor was a skinny bile duct . Second, patients with preoperative stenting tend to have a thicker bile duct than those without one, due to chronic inflammation or fibrosis resulting from stent placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the common hepatic duct (CHD) size of patients with a stent must be larger than that of those without one, even after biliary decompression. Duconseil et al demonstrated that bile duct size <5 mm was significantly associated with the occurrence of biliary stricture, and the only identified risk factor was a skinny bile duct . Second, patients with preoperative stenting tend to have a thicker bile duct than those without one, due to chronic inflammation or fibrosis resulting from stent placement.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about its clinical features including incidence and risk factors. Moreover, although there have been four studies describing HJ stenosis, a detailed operative technique for establishing anastomosis was not unified in each reports . On the other hand, we have performed HJ after PD in a consistent manner, with single layered continuous suture without stent, for all of our patients since 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic duct width is strongly (inversely) related to POPF risk and was included in over half the scoring systems reviewed. Pre‐operative measurement using CT was utilized in three scores and intra‐operative assessment in 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Biliary leakage may originate from injury of the bile ducts, or from anastomotic leakage after bilio-enteric anastomosis. Literature shows an incidence from 2% to 10% after pancreatic surgery without iatrogenic biliary injury; if biliary injury occurred incidence may rise up to 24% ( Table 1) (1,3,4,(11)(12)(13)(14)(15). A multivariate analysis has shown that there are no independent risk factors to predict bile leakage (4).…”
Section: Review Articlementioning
confidence: 99%